The Influence of Leadership Style on the Performance of Generation Z Employees through Job Satisfaction and Job Motivation in West Bandung Regency - Sanjaya, Sanjay (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the impact of leadership styles on the performance of Generation Z employees, with job satisfaction and work motivation as mediating variables. Generation Z, characterized by their digital connectivity and desire for flexible working conditions, is the primary focus of this research. Data was collected through questionnaires from 208 respondents in West Bandung Regency. Data analysis was conducted using Partial Least Squares (PLS) approach. The results show that leadership styles have a positive and significant impact on employee performance both directly and through job satisfaction and work motivation. These findings support the theories of Abraham Maslow, McClelland, and Herzberg, emphasizing the importance of fulfilling needs and motivation to enhance performance. The study's implications provide recommendations for organizations to adopt leadership styles suitable for Generation Z.